Crypto basics : a nontechnical introduction to creating your own money for investors and inventors - Gomzin, Slava (Apress, 2022)
Use this practical, step-by-step guide for developers and entrepreneurs to create and run your own cryptocurrency. Author Slava Gomzin has created two cryptocurrencies and describes in this book the technology and economics of cryptocurrencies as preparation for crypto trading, investing, and other business activities. A detailed overview of special topics includes security, privacy, and usability of crypto as a mainstream payment system. Part I, Understanding Crypto, explains the technology and economic, security, and usability aspects of crypto. This is an introduction to the world of cryptography, blockchain tech, and other elements of crypto such as security, privacy, and a detailed review of payment processing. Part II, Using Crypto, provides the practical knowledge you need to dive into the crypto business such as investment, trading, and even creating your own crypto project. Part III, Creating Your Own Crypto, teaches you how to launch your own crypto project and create your own cryptocurrency.